The Importance Factors in Selecting Extensively Hydrolyzed Formulas for Cow’s Milk Allergy Management - Wasito, Erika; Murti, Laksmi (Journal of Indonesian Specialized Nutrition, 2023)
Current guidelines recommend extensively hydrolyzed formulas (eHF) as the first choice for infants with mild to moderate cow’s milk allergy (CMA) symptoms. Different eHF producers may apply different technical processes that can influence the end characteristics of the products, the efficacy and effectiveness in CMA management. Thi s review aims to summarizes references and reports to indicate the importance factors that should be considered in selecting eHF available in the market for CMA treatment. The most important factor is the clinical evidence on tolerance level of the eHF formula above 90% among allergic children or the efficacy and effectiveness in CMA management. Other factors are the composition of protein molecular size in the end product and the long history of usage of the product in the population with positive feedback from more than 90% healthcare professionals that could indicate as the real-world evidence.